The Church in the World: Shifting Notions of Ecclesial Identity among North American Mennonites - Schmidt Roberts, Laura (Dialog, 2012)
At mid-century, Harold S. Bender's “The Anabaptist Vision” provided a definition of sixteenth-century Anabaptist tradition that clarified the self-understanding of its contemporary Mennonite heirs and by which their faithfulness to the tradition might be judged. Critics of the vision, such as J. Lawrence Burkholder, sought reformulations of the vision's central tension between separation from and integration into “the world,” calling for greater social responsibility and for a recognition that the ambiguities of human existence extend to the church, of necessity qualifying its lived expressions of radical discipleship.